Between Roman Culture and Local Tradition Roman Provincial Coinage of Bithynia and Pontus during the Reign of Trajan (98-117 AD) - Zając, Barbara (2023)
Between Roman Culture and Local Tradition presents a detailed analysis of the Roman provincial coinage of Bithynia and Pontus during the reign of Trajan (98-117), when 14 cities struck coins. The book characterises individual mints, the rhythm of monetary production, iconography and legends, and considers the attribution and dating of individual issues. Context is provided by studies on other categories of artefacts discovered in the local area, including epigraphic and material ones, such as fine art, sculptures and architectural remains. The extent of circulation is also analysed, as well as the coinage of the border centres of neighbouring provinces such as Thrace, Asia and Galatia-Cappadocia. Reference is made to historical sources, principally the correspondence of Pliny the Younger with the emperor, which can help to show the realities of life for the inhabitants of individual centres, including ongoing construction projects or local problems. Overall the book aims to reconstruct the coinage policy of individual cities and culture and religion in various centres during this period, as well as contacts and relationships among the local communities. In turn, the studies of individual cities allow for the creation of a general picture of coinage in the province.